2009
DOI: 10.1080/10412905.2009.9700193
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Essential Oils of Mint and Peppermint as Well as Some of Their Main Compounds

Abstract: The oil of peppermint (Mentha x piperita L.) from the USA, a dementholized cornmint oil (M. canadensis L.), and a fraction of the dementholized cornmint oil were analyzed by GC-FID and GC/MS. The main constituents of the three samples analyzed were menthone (23.4%, 20.4% and 58.3%, respectively) and menthol (40.7%, 41.2% and 12.3%, respectively). The two oils, the cornmint oil fraction and seven mint oil compounds [(-)-menthol, (-)-menthone, (+/-)-menthyl acetate, 1,8-cineole, limonene, b-pinene and b-caryophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 11 publications
4
37
0
Order By: Relevance
“…The results are according to Nance and Setzer [52], who reported that the main constituents of hop-essential oil derived from Saaz variety are ␤-myrcene, ␣-humulene, and ␤-caryophyllene. These compounds are interesting from the standpoint of pharmacological, because of their antimicrobial activity [55] as well as to their anti-inflammatory effects [56]. On the other hand, limonene (6) and ␤-pinene (4) have been reported as antitumor [57] and antimicrobial [55] agents, respectively.…”
Section: Determination Of Terpenoid Metabolites In Hop-essential Oil mentioning
confidence: 99%
See 1 more Smart Citation
“…The results are according to Nance and Setzer [52], who reported that the main constituents of hop-essential oil derived from Saaz variety are ␤-myrcene, ␣-humulene, and ␤-caryophyllene. These compounds are interesting from the standpoint of pharmacological, because of their antimicrobial activity [55] as well as to their anti-inflammatory effects [56]. On the other hand, limonene (6) and ␤-pinene (4) have been reported as antitumor [57] and antimicrobial [55] agents, respectively.…”
Section: Determination Of Terpenoid Metabolites In Hop-essential Oil mentioning
confidence: 99%
“…These compounds are interesting from the standpoint of pharmacological, because of their antimicrobial activity [55] as well as to their anti-inflammatory effects [56]. On the other hand, limonene (6) and ␤-pinene (4) have been reported as antitumor [57] and antimicrobial [55] agents, respectively. Biological activities and odor description of some plant secondary metabolites found in hop-essential oil derived from Saaz variety are summarized in Table 3.…”
Section: Determination Of Terpenoid Metabolites In Hop-essential Oil mentioning
confidence: 99%
“…( Leopold et al 2009). Studies on Antimicrobial activities of different forms of Peppermint viz., aqueous, infusion, decoction, juice and essential oil against 11 different species of Gram-negative bacilli has also been done 9 .…”
Section: Issn: 0975-8232mentioning
confidence: 99%
“…Menthone (44) Z. clinopodioides (6.2%-13.3%) [238] Antifungal effect against C. albicans, synergy with fluconazol [239]; antimicrobial activity against tested strains of bacteria, yeast and pathogenic fungi [240,241] Insecticidal activity tested against various stored grain pests and vectors [242]; moderate insecticidal activity against Sitophilus zeamais [243] Antidepressant-like effects in an unpredictable chronic mild stress mouse model of depression [244] Molecules 2016, 21, 826 16 of 53…”
Section: P-mentha-38-diene (40)mentioning
confidence: 99%
“…rigida (17.4%) [21] p-Menth-4-en-3-one (47) Z. tenuior (0.5%) [202] n.f. Menthone (44) Z. clinopodioides (6.2%-13.3%) [238] Antifungal effect against C. albicans, synergy with fluconazol [239]; antimicrobial activity against tested strains of bacteria, yeast and pathogenic fungi [240,241] Insecticidal activity tested against various stored grain pests and vectors [242]; moderate insecticidal activity against Sitophilus zeamais [243] Antidepressant-like effects in an unpredictable chronic mild stress mouse model of depression [244] O Piperitone (45) Z. clinopodioides (4.18%) [11] Repellent activity against ants of the genus Crematogaster [245]; insecticidal activity against larvae of Spodoptera littoralis [246] and against Callosobruchus maculatus [247] Increase in antimicrobial activity of furazolidone and nitrofurantoin against bacteria of the family Enterobacteriaceae [248,249] Fungicidal activity against Aspergillus flavus [250] O Z. clinopodioides subsp. rigida (1.4%) [21] Z. clinopodioides subsp.…”
mentioning
confidence: 99%